Impact of Visceral Fat on Skeletal Muscle Mass and Vice Versa in a Prospective Cohort Study: The Korean Sarcopenic Obesity Study (KSOS) - Kim, Tae Nyun; Park, Man Sik; Ryu, Ja Young; Choi, Hae Yoon; Hong, Ho Cheol; Yoo, Hye Jin; Kang, Hyun Joo; Song, Wook; Park, Seok Won; Baik, Sei Hyun; Newman, Anne B.; Choi, Kyung Mook (PloS one, 2014)
Sarcopenia and visceral obesity have been suggested to aggravate each other, resulting in a vicious cycle. However, evidence based on prospective study is very limited. Our purpose was to investigate whether visceral fat promotes a decrease in skeletal muscle mass and vice versa. We observed changes in anthropometric and body composition data during a follow-up period of 27.6 ± 2.8 months in 379 Korean men and women (mean age 51.9 ± 14.6 years) from the Korean Sarcopenic Obesity Study (KSOS). Appendicular lean soft tissue (ALST) mass was calculated using dual-energy X-ray absorptiometry, and visceral fat area (VFA) was measured using computed tomography at baseline and follow-up examination. ALST mass significantly decreased, whereas trunk and total fat mass increased in both men and women despite no significant change in weight and body mass index. In particular, women with visceral obesity at baseline had a greater decrease in ALST mass than those without visceral obesity (P = 0.001). In multiple linear regression analysis, baseline VFA was an independent negative predictor of the changes in ALST after adjusting for confounding factors including age, gender, life style and body composition parameters, insulin resistance, high sensitivity C-reactive protein and vitamin D levels (P = 0.001), whereas the association between baseline ALST mass and changes in VFA was not statistically significant (P = 0.555). This longitudinal study showed that visceral obesity was associated with future loss of skeletal muscle mass in Korean adults. These results may provide novel insight into sarcopenic obesity in an aging society.